Investigation on the Attention Deficit Hyperactivity Disorder Effect on Infatuation and Impulsivity in Adolescents - Soares, Lorrayne Stephane; Costa, Danielle de Souza; Malloy-Diniz, Leandro Fernandes; Romano-Silva, Marco Aurélio; de Paula, Jonas Jardim; de Miranda, Débora Marques (Frontiers in Behavioral Neuroscience, 2019)
Objective: To investigate the association between infatuation/passionate love and impulsivity in a context of potential high impulsivity: adolescents with attention deficit and hyperactivity/impulsivity (ADHD) diagnosis compared with typically developing. Method: Impulsivity was understood as an exploratory and a sensation seeking behavior, and evaluated using the UPPS Impulsive Behavior Scale. Eighty-one adolescents from 13-to-18 years old with and without ADHD diagnosis were compared regarding infatuation intensity, behavioral impulsivity, and social and educational profiles. Results: After correlation analysis, we found association between higher scores on the infatuation intensity with fewer years of formal education, heightened urgency and sensation seeking. On the other hand, using the generalized equation model, we showed that the association of passionate love with behavioral urgency and sensation seeking did not change in the presence of the ADHD diagnosis. Conclusion: The understanding of the relationship of impulsivity with infatuation might help to clarify why some population groups show an increased risk for negative social outcomes.